1995
DOI: 10.1111/j.1365-2141.1995.tb05192.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cytokine production by bone marrow stromal cells of immunodeficient mice

Abstract: The aetiology of the bone marrow suppression in HIV-infected patients is unknown. We have demonstrated previously that the ability of bone marrow cells, derived from mice made immunodeficient by infection with the retrovirus LP-BM5, to establish long-term stromal cultures is impaired. In this study we determined the ability of bone marrow stromal cells from these immunodeficient mice to produce cytokines important in haemopoiesis. Neither SCF, IL-3, GM-CSF nor TNF alpha were found in conditioned media of long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In vivo and in vitro studies have suggested both a direct effect on stem progenitor cells and an indirect effect via cells of the bone marrow environment. 23,35,36 Further studies are required to elucidate the mechanism whereby clinically asymptomatic HIV infection might cause depressed erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro studies have suggested both a direct effect on stem progenitor cells and an indirect effect via cells of the bone marrow environment. 23,35,36 Further studies are required to elucidate the mechanism whereby clinically asymptomatic HIV infection might cause depressed erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have failed to demonstrate a clear constitutive upregulation of these substances, namely, TGF-b, TNF-a and IL-1b in HIV patients. Instead, deficiency of hematopoietic growth factors, such as the stem cell factor (SCF), were observed [46,71].…”
Section: Bone Marrow Microenvironmentmentioning
confidence: 99%
“…Since Hamburger et al first reported that BMMSCs produce immuno-cytokines to contribute to the suppression of hematopoiesis ( 36 ), the immunomodulatory effects of MSCs and their underlying mechanisms have been of interest to investigators. In 2005, the first most-cited article innovatively described the phenomenon of MSCs regulating allogeneic immune cells, suggesting that prostaglandin E2 (PGE2) may be an important MSC immunomodulator ( 5 ).…”
Section: Discussionmentioning
confidence: 99%